R-loop landscape in mature human sperm: Regulatory and evolutionary implications - Scheuren, Maurice; Möhner, Jonas; Zischler, Hans (Frontiers in Genetics, 2023)
R-loops are three-stranded nucleic acid structures consisting of an RNA-DNA hybrid and a displaced DNA strand. While R-loops pose a potential threat to genome integrity, they constitute 5% of the human genome. The role of R-loops in transcriptional regulation, DNA replication, and chromatin signature is becoming increasingly clear. R-loops are associated with various histone modifications, suggesting that they may modulate chromatin accessibility. To potentially harness transcription-coupled repair mechanisms in the germline, nearly the entire genome is expressed during the early stages of male gametogenesis in mammals, providing ample opportunity for the formation of a transcriptome-dependent R-loop landscape in male germ cells. R-loop turnover is mediated by RNase H enzymes that hydrolyze the RNA strand of RNA/DNA hybrids, with RNase H2 activity as the predominant source. RNase H2 is present in the early stages of murine spermatogenesis, whereas no expression was detected in differentiated spermatids. In this study, our data demonstrated the presence of R-loops in fully mature human and bonobo sperm heads and their partial correspondence to transcribed regions and chromatin structure, which is massively reorganized from mainly histone to mainly protamine-packed chromatin in mature spermatids. The sperm R-loop landscape resembles characteristic patterns of somatic cells. Surprisingly, we detected R-loops in both residual histone and protamine-packed chromatin and localize them to still-active retroposons, Alus and SVAs, the latter has recently arisen in hominoid primates. We detected both evolutionarily conserved and species-specific localizations. Comparing our DRIP data with published DNA methylation and histone ChIP data, we hypothesize that R-loops epigenetically reduce methylation of SVAs. Strikingly, we observe a strong influence of R-loops on the transcriptomes of zygotes from early developmental stages before zygotic gene activation. Overall, these findings suggest that chromatin accessibility influenced by R-loops may represent a system of inherited gene regulation.